Pengaruh Religiusitas, Persepsi Dan Motivasi Nasabah Terhadap Keputusan Memilih Perbankan Syariah - Muhammad Zuhirsyan; Nurlinda Nurlinda (JPS (Jurnal Perbankan Syariah), 2021)
This research aims to see how much influence religiosity, perception, and motivation have on choosing Islamic banking. This research is quantitative research with data collection methods using survey methods and questionnaires. Samples were selected by non-probability sampling and convenience sampling. Questionnaires were distributed to 96 CIMB Niaga Syariah Medan customers, and 61 questionnaires were returned. Data analysis using multiple regression test using SPSS tool. The study results found simultaneously that religiosity, perception, and motivation influenced the decision to choose Islamic banking. Partially, motivation has a positive effect on the decision to choose Islamic banking. In contrast, religiosity has a negative value and does not affect the decision to choose Islamic banking and perception, does not affect the decision to choose Islamic banking.